Production cost analysis using full costing method of crystal guava business in bantarsari village - Nurlaela, Arini; Gandhy, Abel; Zaini, Oktori Kiswati (Jurnal Mantik, 2025)
Crystal guava contains many nutrients such as vitamins B and A, as well as antioxidants that are good for health, such as boosting the immune system, aiding digestion, improving skin health, and reducing the risk of heart disease. Conducting a cost analysis is an important step that must be taken by business operators. The purpose of this study is to assist crystal guava farmers in Bantarsari in achieving fair profits through an analysis of the Production Cost Analysis for Crystal Guava Fruit in Bantarsari Village, aiming to determine the appropriate and competitive selling price for this business. Production Cost Analysis can be conducted using either the Full Costing or Variable Costing method. In this study, the Full Costing method was used, where the researcher included all production costs, such as fixed costs and variable costs, in the COGS calculation analysis. From the analysis conducted, the COGS was determined to be Rp 3,173 per kilogram, meaning that this price is the minimum selling price that can be applied for the business to reach the break-even point, where income and expenses are balanced